Desempenho de gotejadores e produção de capim elefante (Pennisetum purpureum Schum.) com percolado de aterro sanitário no semiárido - Mesquita, Francisco de Oliveira (Universidade Federal Rural do Semi-Árido, 2016)
With the establishment of the National Solid Waste Policy in Brazil, it is expected that the number of landfills increase, over the years, and with it the need for the development of treatment techniques, or use of leachate. The objective of this work is to analyze the effects of the application of landfill leachate in performance of dripper units, production of biomass and phytoextraction capacity of elephant grass (Pennisetum purpureum Schum) and chemical attributes of a ultisol. For this, there were two studies on Experimental Station of Water Reuse of the Universidade Federal Rural do Semi-Árido (UFERSA): a) In the first study, the experiment was conducted in a split plot scheme, with types of drippers (G1, G2, G3 and G4) in the plots and evaluation times (0, 20, 40, 60, 80, 100, 120, 140 and 160 hours) in the subplots, with a completely randomized design and four replications. In the four dripper units supplied with landfill leachate diluted in public water supply, evaluated the hydraulic performance indicators and the quality of the circulating fluid, every 20 h until 160 h. At the end of the trial, were identified agents of clogging; and b) In the second study, we used 25 land plots, each of the dimensions of 1.0 x 1.0 m, which was cultivated elephant grass for 83 days. The experiment was conducted in a randomized block design on split plot scheme, with five treatments (T1-irrigated plots only with the public water supply, T2 - 50% of the effluent dose by criterion of the Environmental Protection Agency US-EPA plus public water supply, T3 - 100% of the effluent dose by EPA criterion plus public water supply, T4 - 150% of the effluent dose by EPA criterion more public water supply and T5 - 200% of the dose effluent by criterion EPA plus public water supply) in the parcels and five analysed depths (0.00 to 0.10, 0.10 to 0.20, 0.20 0.30, 0.30 to 0 40 and from 0.40 to 0.50 m) in the subplots, with five repetitions. There was statistical difference G1 dripper clogging levels in relation to the others, indicating less susceptible to clogging of drippers G2, G3 and G4. The elephant grass plants were nutritionally balanced N, P, K, Ca, Mg, Fe, Mn, Fe, Cu. The elephant grass have a high ability to extract ions from the soil solution to the roots and to transfer from the roots to the aerial part and, especially potentially toxic heavy metals such as Ni, Cd and Pb. A significant change in pH values, N , P, Mg, Cu, Mn, Fe, Zn, Ni, Cd and Pb soil due to the successive applications of landfill leachate dilutions in public water supply. The T3 treatment was the most recommended for elephant grass production in ultisol
Keywords: Resíduos; Reuso; Emissores; Gramínea; Fitoextração; Waste; Reuse; Emitters; Grassy; Phytoextraction; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO